Chondrichthyan tooth enameloid: past, present, and future. (3rd March 2015) - Enault, Sébastien; Guinot, Guillaume; Koot, Martha B.; Cuny, Gilles
<x xml:space="preserve">Abstract</x> Enameloid is a hard mineralized tissue covering chondrichthyan and actinopterygian teeth. Over the past 40 years, it has been extensively studied in various extinct and extant sharks, leading to the broad use of microstructural characters to differentiate between hybodont and neoselachian teeth. However, the chondrichthyan taxic diversity is disproportionately high compared to the number of taxa explored for enameloid microstructure, and the generalization of these few observations to the whole group is problematic. Indeed, many other groups, in particular modern rays and skates, have been completely overlooked, and almost nothing is known about their tooth histology. Furthermore, the recent discovery of typical neoselachian character in cladodontomorph sharks teeth clearly indicates that we have had an over‐simplified perception of the chondrichthyan enameloid distribution, which put into question the previously proposed evolutive scenarios dealing whith this tissue. We propose a brief historical overview of the study and understanding of chondrichthyan enameloid diversity and briefly discuss preparation issues encountered when dealing with the study of chondrichthyan hypermineralized tissues. Then, the variation of enameloid microstructures encountered in ctenacanthiforms, hybodonts, selachimorphs, and batomorphs is explored, summarized, and discussed. Although the full extent of the diversity and variability of the enameloid microstructure in many of these groups and others remains to be fully determined, we are able to show that most possess a much more complex enameloid microstructure than expected, and propose a revised and more fitting chondrichthyan enameloid terminology, based on the recognition of two main units: an external Single Crystallite Enameloid (SCE) and an internal Bundled Crystallite Enameloid (BCE). Our study reveals new insights in the understanding of character distribution among batomorphs and sets a framework for tackling global chondrichthyan tooth enameloid evolution. © 2015 The Linnean Society of London